2016
DOI: 10.3389/fpls.2016.01035
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Physiological Analyses Reveal Putrescine Responses in Roots of Cucumber Stressed by NaCl

Abstract: Soil salinity is a major environmental constraint that threatens agricultural productivity. Different strategies have been developed to improve crop salt tolerance, among which the effects of polyamines have been well-reported. To gain a better understanding of the cucumber (Cucumis sativus L.) responses to NaCl and unravel the underlying mechanism of exogenous putrescine (Put) alleviating salt-induced damage, comparative proteomic analysis was conducted on cucumber roots treated with NaCl, and/or Put for 7 da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 65 publications
2
30
0
Order By: Relevance
“…However, the remaining three PDI proteins (spots 42, 44, and 45) were significantly decreased by pathogen attack (inoculated with FOC). This effect may be due to the stresses that were inhibited expression of this type of protein, which was consistent with previous reports (Yuan et al, 2016). However, another report showed that the application of PGPR recovered the expression level of this protein under stress conditions (Li et al, 2013b).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, the remaining three PDI proteins (spots 42, 44, and 45) were significantly decreased by pathogen attack (inoculated with FOC). This effect may be due to the stresses that were inhibited expression of this type of protein, which was consistent with previous reports (Yuan et al, 2016). However, another report showed that the application of PGPR recovered the expression level of this protein under stress conditions (Li et al, 2013b).…”
Section: Discussionsupporting
confidence: 93%
“…HSP70 can be induced by various environmental stresses, such as cold, salt, high temperature, and hypoxic stress, and this protein often acts as a molecular chaperone (Xu et al, 2011; Li et al, 2013b; Yuan et al, 2016) to prevent the irreversible aggregation of other proteins and regulate the folding and accumulation of proteins (Feder and Hofmann, 1999). In this study, it was observed that NSY50 enhances the expression of HSP70 (spot 4) by 3.31-fold compared to the control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations